2017
DOI: 10.18632/oncotarget.23658
|View full text |Cite
|
Sign up to set email alerts
|

Age at menarche and risks of gestational diabetes mellitus: a meta-analysis of prospective studies

Abstract: BackgroundAccumulating evidence suggests that early menarche is associated with adult obesity, which in turn may increase the risk of insulin resistance and hyperglycemia. However, the relation of menarcheal age with gestational diabetes mellitus (GDM) remains inconsistent across studies. The objective of this meta-analysis was to evaluate the association between age at menarche and GDM risk.Materials and MethodsWe searched Medline (PubMed), Embase, Web of Knowledge and the Cochrane library through the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In Asia, the prevalence of GDM ranges from 0.7 to 51.0% [28–30]. This vast disparity in prevalence rates may be due to differences in ethnicity [28, 30], diagnostic criteria [3133], screening strategies [29, 34], and population characteristics [35, 36].…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, the prevalence of GDM ranges from 0.7 to 51.0% [28–30]. This vast disparity in prevalence rates may be due to differences in ethnicity [28, 30], diagnostic criteria [3133], screening strategies [29, 34], and population characteristics [35, 36].…”
Section: Introductionmentioning
confidence: 99%
“…The precise mechanism by which early age at menarche may increase the risk of GDM is not clear. Some studies indicated that the early age at menarche was a risk factor of GDM [1214]. Additionally, Early age at menarche has been associated with risk factors for GDM such as excessive pre-pregnancy obesity [1517], insulin resistance [18], and hormonal changes [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of GDM varies worldwide based on population characteristics (e.g. maternal age, socioeconomic status or body composition) (Huvinen et al, 2018;Xiao et al, 2018), race/ ethnicity (Alfadhli et al, 2015) and diagnostic criteria used for screening (Harper et al, 2016;Adam and Rheeder, 2017;Lauring et al, 2018;Nguyen et al, 2018). It has been reported that GDM affects between 1% and 28% of pregnant women worldwide (Jiwani et al, 2012).…”
Section: Prevalence Of Gestational Diabetes Mellitusmentioning
confidence: 99%